Photoelectric conversion element, photoelectric conversion module having the same, photoelectric conversion device, mobile body, and building material

JP2022168820A5Active Publication Date: 2025-02-17CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022015369
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-26
Filing Date
2022-02-03
Publication Date
2025-02-17
Estimated Expiration
2042-02-03

AI Technical Summary

Technical Problem

Existing organic solar cells face challenges in achieving high photoelectric conversion efficiency due to difficulties in maintaining charge transport material distances and forming phthalocyanine compounds in an amorphous state, which hinders optimal performance.

Method used

A photoelectric conversion element is designed with a photoelectric conversion layer containing an organic-inorganic perovskite compound between electrodes, and a particle layer composed of phthalocyanine compounds is introduced between the conversion layer and the first electrode, enhancing interfacial bonding and maintaining crystallinity.

Benefits of technology

This configuration results in a photoelectric conversion element with significantly improved efficiency, enabling applications in modules, devices, moving objects, and building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a photoelectric conversion element with a higher photoelectric conversion efficiency.SOLUTION: The photoelectric conversion element has a first electrode 7, a second electrode 3, and a photoelectric conversion layer 5 including an organic-inorganic perovskite compound arranged between the first electrode 7 and the second electrode 3. A particle layer 6 composed of particles mainly of a phthalocyanine compound is arranged between the photoelectric conversion layer 5 and the first electrode 7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photoelectric conversion element, a photoelectric module having the photoelectric conversion element, a photoelectric conversion device, a moving body, and a building material.

Background Art

[0002] In order to solve the problems of depletion of fossil energy and environmental problems of the earth caused by the use of fossil energy, research on renewable and clean alternative energy sources such as solar energy, wind power, and hydraulic power has been actively conducted. Among them, the interest in solar cells that directly convert electrical energy from sunlight has been greatly increasing. Here, a solar cell means a battery that absorbs light energy from sunlight and generates a current-voltage by utilizing the photovoltaic effect in which electrons and charges are generated. Currently, n-p diode type silicon (Si) single crystal-based solar cells having a light energy conversion efficiency exceeding 20% are widely known and are actually used for solar power generation. However, these have problems in that they require a high-temperature treatment process and the cost of the material itself is high, so the cost per unit power is high. Also, from the perspective of silicon resources, there are problems in supply. On the other hand, solar cells using organic materials (hereinafter referred to as "organic solar cells") do not require a high-temperature process, can be produced in a so-called roll to roll manner on a sheet-like substrate, and can reduce costs. Further improvement in power generation efficiency and durability is desired for the practical application of organic solar cells. Particularly, phthalocyanine compounds are being developed as materials for the practical application of organic solar cells because of their excellent light absorption properties, charge transport properties, and chemical stability. For example, Patent Document 1 discloses that in an organic solar cell having a bulk heterojunction structure, the photoelectric conversion efficiency is improved by using phthalocyanine particles as a light absorber. Also, Patent Document 2 discloses that in an organic solar cell using a perovskite compound in a photoelectric conversion layer, an organically modified phthalocyanine compound is dissolved in an organic solvent and applied and formed into a film on the photoelectric conversion layer, thereby improving the power generation efficiency.

Prior Art Documents

[0003] [Patent Document 1] Japanese Patent Publication No. 2012-119405 [Patent Document 2] Japanese Patent Publication No. 2016-139805 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] The method disclosed in Patent Document 1 requires the charge transport material, electron transport material, and light absorber to be arranged at equal distances in order to achieve high power generation efficiency, which presents a challenge in practical application. Furthermore, the method disclosed in Patent Document 2 involves the deposition of the phthalocyanine compound in an amorphous state, which prevents the inherent charge transport ability from being expressed, making it difficult to achieve high photoelectric conversion efficiency. The object of the present invention is to provide a photoelectric conversion element with even higher photoelectric conversion efficiency, and further, to provide a device such as a photoelectric conversion apparatus using such a photoelectric conversion element. [Means for solving the problem]

[0005] The first aspect of the present invention is a photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer containing an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, The present invention is characterized by having a particle layer consisting mainly of phthalocyanine compounds between the photoelectric conversion layer and the first electrode. The second aspect of the present invention is a photoelectric conversion module characterized by having a plurality of the first photoelectric conversion elements of the present invention described above. The third aspect of the present invention is a photoelectric conversion device characterized by having the first photoelectric conversion element of the present invention described above, and a power storage unit or inverter connected to the photoelectric conversion element. The fourth aspect of the present invention is a mobile body characterized by comprising a photoelectric conversion element and a body equipped with the photoelectric conversion element. The fifth aspect of the present invention is a building material characterized by comprising the first photoelectric conversion element of the present invention, a protective member for protecting the photoelectric conversion element, and a heat dissipation member. [Effects of the Invention]

[0006] According to the present invention, a photoelectric conversion element with even higher photoelectric conversion efficiency is provided, and by using such a photoelectric conversion element, a photoelectric conversion module, a photoelectric conversion device, a mobile body, and building materials with high photoelectric conversion efficiency can be provided. [Brief explanation of the drawing]

[0007] [Figure 1] This is a schematic cross-sectional view in the thickness direction of one embodiment of the photoelectric conversion element of the present invention. [Figure 2] This is a schematic perspective view showing one embodiment of a mobile body equipped with the photoelectric conversion element of the present invention. [Figure 3] This is a schematic perspective view showing one embodiment of a building material equipped with the photoelectric conversion element of the present invention. [Modes for carrying out the invention]

[0008] The photoelectric conversion element of the present invention is a photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer containing an organic-inorganic perovskite compound disposed between the first electrode and the second electrode. Furthermore, the present invention is characterized in that a particle layer consisting mainly of particles of a phthalocyanine compound is provided between the photoelectric conversion layer and the first electrode.

[0009] The particle layer according to the present invention is formed by dispersing particles having a phthalocyanine compound in an organic solvent and coating it onto a photoelectric conversion layer. The inventors have found that having such a particle layer results in a photoelectric conversion element with excellent photoelectric conversion efficiency. The reason why high photoelectric conversion efficiency is obtained in the present invention is not yet clear, but it is thought to be as follows: By forming a film of phthalocyanine compound in a particle state, high crystallinity is maintained, and the inherent charge transport ability of phthalocyanine can be expressed. Furthermore, when the photoelectric conversion layer contains an inorganic perovskite compound, submicron-scale irregularities are created on the surface, and it is presumed that filling these irregularities with phthalocyanine particles improves interfacial bonding, thereby achieving extremely high photoelectric conversion efficiency.

[0010] In this specification, "layer" refers not only to layers with clear boundaries or flat, thin films, but also to layers with gradually changing elemental concentrations and layers that can form complex, interwoven structures with other layers. Furthermore, elemental analysis of a layer can be performed, for example, by FE-TEM / EDS line analysis of a cross-section of a photoelectric conversion element to confirm the elemental distribution of specific elements.

[0011] The embodiments of the present invention will be described in detail below. The present invention is not limited to the embodiments described below, and the scope of the present invention also includes modifications, improvements, etc., to the embodiments described below, based on the ordinary knowledge of those skilled in the art, without departing from the spirit of the invention.

[0012] Figure 1 is a schematic cross-sectional view showing the configuration of one embodiment of the photoelectric conversion element of the present invention. The substrate 2 has a second electrode 3, an electron transport layer 4, a photoelectric conversion layer 5, a particle layer 6, and a first electrode 7. One of the first electrode 7 and the second electrode 3 is the anode and the other is the cathode, and current is generated in the configuration in which the first electrode 7 and the second electrode 3 are connected by an external circuit.

[0013] The photoelectric conversion layer 5 is excited by light incident through the substrate 2, the second electrode 3, the electron transport layer 4, or the first electrode 7 and the particle layer 6, generating electrons or holes. That is, the photoelectric conversion layer 5 generates a current between the first electrode 7 and the second electrode 3. The electron transport layer 4 is a layer disposed between the photoelectric conversion layer 5 and the two electrodes 3 and 7, and may not be formed in some cases. The electron transport layer 4 and the photoelectric conversion layer 5 may be stacked in multiple layers. Such a form can also be called a tandem structure.

[0014] (Substrate) The photoelectric conversion element 1 of the present invention may include a substrate 2. For example, transparent glass substrates such as soda lime glass and alkali-free glass, ceramic substrates, transparent plastic substrates, etc. can be mentioned. When taking in light from the first electrode 7 side, the substrate 2 can use an opaque material, and when taking in light from the second electrode 3 side, the substrate 2 is composed of a transparent material.

[0015] (Electrode) The materials of the first electrode 7 and the second electrode 3 are not particularly limited, and conventionally known materials can be used. For example, metals such as gold, silver, titanium, and copper, sodium, sodium-potassium alloy, lithium, magnesium, aluminum, magnesium-silver mixture, magnesium-indium mixture, aluminum-lithium alloy, Al / Al2O3 mixture, Al / LiF mixture, etc. can be mentioned. As transparent electrode materials, for example, conductive transparent materials such as CuI, ITO (indium tin oxide), SnO2, AZO (aluminum zinc oxide), IZO (indium zinc oxide), GZO (gallium zinc oxide), FTO (fluorine-doped tin oxide), ATO (antimony-doped tin oxide), etc., and conductive transparent polymers can be mentioned. These materials may be used alone or in combination of two or more. At least one of the first electrode 7 and the second electrode 3 on the light incident side is a transparent electrode, and the other may be a transparent electrode or may also serve as a reflective layer formed of a light-reflective material, or may be a transparent electrode provided with a reflective layer on the side opposite to the light incident side. When the first electrode 7 is on the light incident side, the second electrode 3 can be used as a transparent electrode and the substrate 2 can be used as a reflective layer. Incidentally, the transparent electrode is often a patterned electrode.

[0016] (Photovoltaic conversion layer) The photovoltaic conversion layer 5 contains an organic-inorganic perovskite compound represented by the general formula R-M-X3 (where R is an organic molecule, M is a metal atom, and X is a halogen atom or a chalcogen atom). By using the organic-inorganic perovskite compound in the photovoltaic conversion layer 5, the photovoltaic conversion efficiency of the solar cell can be improved.

[0017] In the above general formula, R is an organic molecule, and C p N m H n (p, m, and n are all positive integers). Preferably, the R is specifically, for example, methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentylamine, dihexylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, tripentylamine, trihexylamine, ethylmethylamine, methylpropylamine, butylmethylamine, methylpentylamine, hexylmethylamine, ethylpropylamine, ethylbutylamine, imidazole, azole, pyrrole, aziridine, azirine, azetidine, azeto, imidazoline, carbazole, aniline, pyridine, methylcarboxylamine, ethylcarboxylamine, propylcarboxylamine, butylcarboxylamine, pentylcarboxylamine, hexylcarboxylamine, formamidinium, ions of guanidine (such as methylammonium (CH3NH3), etc.), and phenethylammonium. Among them, methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, aniline, pyridine, propylcarboxylamine, butylcarboxylamine, pentylcarboxylamine, formamidinium, ions of guanidine, and phenethylammonium are preferred, and methylamine, ethylamine, propylamine, pentylcarboxylamine, formamidinium, and ions of guanidine are more preferred.

[0018] The above M is a metal atom, and examples include lead, tin, bismuth, zinc, titanium, antimony, nickel, iron, cobalt, silver, copper, gallium, germanium, magnesium, calcium, indium, aluminum, manganese, chromium, molybdenum, europium, etc. Among these, lead, tin, and bismuth are preferred from the viewpoint of electron orbital overlap. These metal atoms may be used individually or in combination of two or more.

[0019] The above X is a halogen atom or a chalcogen atom, such as chlorine, bromine, iodine, sulfur, or selenium. These halogen atoms or chalcogen atoms may be used individually or in combination of two or more. Among these, halogen atoms are preferred because the inclusion of a halogen in the structure makes the organic-inorganic perovskite compound more soluble in organic solvents, enabling its application to inexpensive printing methods and the like. Furthermore, iodine is more preferred because it narrows the energy band gap of the organic-inorganic perovskite compound.

[0020] The above organic-inorganic perovskite compound preferably has a cubic crystal structure in which a metal atom M is arranged at the body center, organic molecules R are arranged at each vertex, and halogen atoms or chalcogen atoms X are arranged at the face centers. Although the details are not clear, it is presumed that having such a structure allows the orientation of the octahedra in the crystal lattice to change easily, thereby increasing the electron mobility in the organic-inorganic perovskite compound and improving the photoelectric conversion efficiency of the photoelectric conversion element.

[0021] The organic-inorganic perovskite compound used in this invention is preferably a crystalline semiconductor. A crystalline semiconductor is a semiconductor in which the X-ray scattering intensity distribution can be measured and a scattering peak can be detected. The crystalline nature of the organic-inorganic perovskite compound increases the electron mobility within the compound, thereby improving the photoelectric conversion efficiency of the photoelectric conversion element.

[0022] The thickness of the photoelectric conversion layer according to the present invention is preferably 5 nm or more and 1000 nm or less. If the thickness is 5 nm or more, light can be sufficiently absorbed, and if it is 1000 nm or less, the generated charge can be transported to each electrode. A more preferable lower limit is 10 nm or more, a more preferable upper limit is 700 nm, an even more preferable lower limit is 15 nm, and an even more preferable upper limit is 500 nm.

[0023] In this invention, the maximum surface roughness height Rz of the photoelectric conversion layer 5 is measured as follows. First, the surface of the photoelectric conversion layer 5 is laser-analyzed using a laser microscope (Keyence "VK-X200") at a standard magnification of 150x and a pitch of 0.2 μm. The obtained laser observation image is pre-processed with cutoff values ​​λs = 0.25 μm and λc = 0.25 mm to obtain the maximum surface roughness height Rz.

[0024] (particle layer) The photoelectric conversion element 1 of the present invention has a particle layer 6 consisting mainly of particles of a phthalocyanine compound between the photoelectric conversion layer 5 and the first electrode 7. Preferably, the particles contain 50% by mass or more of the phthalocyanine compound as measured by elemental analysis ratio by ICP / MS, and more preferably 80% by mass or more and 99% by mass or less. When the phthalocyanine compound is 50% by mass or more, the particle stability is high, which is preferable. When the phthalocyanine compound is 80% by mass or more, the π-π stacks within the particles become stronger and the charge transport ability is improved.

[0025] The thickness of the particle layer 6 is preferably 20 nm to 800 nm. If the thickness is 20 nm or more, the photoelectric conversion layer 5 can be sufficiently covered and charge transport can be performed smoothly, and if the thickness is 800 nm or less, charge can be transported well to each electrode. More preferably, the thickness is 50 nm to 600 nm, and even more preferably, 50 nm to 400 nm.

[0026] In the present invention, the average particle size of the particles mainly composed of phthalocyanine compounds has a preferred upper limit of 300 nm and a preferred lower limit of 20 nm. If the average particle size is 300 nm or less, the irregularities of the photoelectric conversion layer 5 can be filled, and the charge generated in the photoelectric conversion layer 5 can be smoothly extracted. If the average particle size is 20 nm or more, the interfacial resistance between particles when filling the irregularities of the photoelectric conversion layer 5 can be reduced, and the charge transport ability can be performed smoothly. A more preferred upper limit for the average particle size is 250 nm, a more preferred lower limit is 60 nm, an even more preferred upper limit is 150 nm, and an even more preferred lower limit is 70 nm.

[0027] The average particle size of particles mainly composed of phthalocyanine compounds can be obtained by using methods such as dynamic light scattering, laser diffraction, gravity sedimentation, ultrasonic attenuation, or image imaging, provided that the primary particle size of the phthalocyanine compound crystalline particles can be measured. In the embodiment of this invention, the average particle size was derived using image imaging with a scanning electron microscope (SEM). Specifically, first, an SEM image of particle layer 6 at 100,000x magnification was used, and crystalline particles (more than 10,000) were extracted using image processing software Photoshop (Adobe). Next, the area S of each crystalline particle was determined, and the diameter of a circle of the same area (= 2 × (S / π)) was calculated. 1 / 2 The average particle size was defined as ).

[0028] In the present invention, it is preferable that the particles mainly composed of phthalocyanine compounds include crystalline particles of a crystalline phthalocyanine compound that exhibit peaks at Bragg angles 2θ of 7.4°±0.3° and 28.2°±0.3° in the X-ray diffraction spectrum using CuKα rays. Furthermore, it is preferable that such particles include crystalline particles of a phthalocyanine compound that have a peak between 20 nm and 50 nm in the crystalline particle size distribution measured using small-angle X-ray scattering, and the full width at half maximum of that peak is 50 nm or less.

[0029] Powder X-ray diffraction measurements of particles mainly composed of phthalocyanine compounds were performed under the following conditions.

[0030] [Powder X-ray diffraction measurement] Measurement equipment used: RINT-TTRII X-ray diffractometer, manufactured by Rigaku Electric Co., Ltd. X-ray tube:Cu X-ray wavelength: Kα1 Tube voltage: 50KV Tube current: 300mA Scanning method: 2θ scan Scan speed: 4.0° / min Sampling interval: 0.02° Starting angle 2θ: 5.0° Stop angle 2θ: 35.0° Goniometer: Rotor horizontal goniometer (TTR-2) Attachment: Capillary rotating sample stage Filter: None Detector: Scintillation counter Incident Monochrome: Use Slit: Variable slit (parallel beam method) Counter monometer: Not used Divergent slit: Open Divergence vertical limiting slit: 10.00 mm Scattering slit: Open Light-receiving slit: Open

[0031] In the present invention, the phthalocyanine compound may have a metal ligand. Examples of coordinating metals include Ga, Cu, and Ti, with Ga being preferred from the viewpoint of crystallinity. The above coordinating metal may have substituents. Examples of substituents include hydroxyl groups and halogen groups, with hydroxyl groups being preferred from the viewpoint of charge transport ability. From these viewpoints, hydroxygallium phthalocyanine is particularly preferred as the phthalocyanine compound.

[0032] In the photoelectric conversion element of the present invention, an electron transport layer may be disposed between the first electrode 7 and the photoelectric conversion layer 5, and / or between the second electrode 3 and the photoelectric conversion layer 5. The photoelectric conversion element 1 shown in Figure 1 is an example in which an electron transport layer 4 is disposed between the second electrode 3 and the photoelectric conversion layer 5.

[0033] The material of the electron transport layer 4 is not particularly limited and includes, for example, N-type conductive polymers, N-type low molecular weight organic semiconductors, N-type metal oxides, N-type metal sulfides, alkali metal halides, alkali metals, surfactants, etc. Specifically, examples include cyano group-containing polyphenylene vinylene, boron-containing polymers, vasocuproin, vasophenanthrene, hydroxyquinolinatoaluminum, oxadiazole compounds, benzimidazole compounds, naphthalenetetracarboxylic acid compounds, perylene derivatives, phosphine oxide compounds, phosphine sulfide compounds, fluoro group-containing phthalocyanines, titanium dioxide, zinc oxide, indium oxide, tin oxide, gallium oxide, tin sulfide, indium sulfide, zinc sulfide, etc.

[0034] The electron transport layer 4 may consist only of a thin-film electron transport layer, but it is preferable that it includes a porous electron transport layer. In particular, when the photoelectric conversion layer 5 is a composite film containing an organic-inorganic perovskite compound, a more complex composite film (a more intricately interwoven structure) can be obtained, and the photoelectric conversion efficiency is higher. Therefore, it is preferable that the composite photoelectric conversion layer 5 is deposited on the porous electron transport layer 4.

[0035] The preferred thickness of the electron transport layer 4 is 1 nm at the lower limit and 2000 nm at the upper limit. If the thickness is 1 nm or more, it can sufficiently block holes, and if it is 2000 nm or less, it will not be a resistance during electron transport and the photoelectric conversion efficiency will be high. A more preferred lower limit for the thickness is 3 nm, a more preferred upper limit is 1000 nm, an even more preferred lower limit is 5 nm, and an even more preferred upper limit is 500 nm.

[0036] (Photoelectric converter) The photoelectric conversion device of the present invention has a plurality of photoelectric conversion elements of the present invention, and when a plurality of photoelectric conversion elements are connected, it can also be called a photoelectric conversion module. The photoelectric conversion elements may be stacked to increase the output voltage. The photoelectric conversion device also has the photoelectric conversion elements of the present invention and an inverter. The inverter may be a converter that converts DC to AC. The photoelectric conversion device may have a power storage unit connected to the photoelectric conversion elements. The power storage unit is not limited as long as it can store electricity. Examples include secondary batteries using lithium ions, all-solid-state batteries, electric double-layer capacitors, etc.

[0037] (Mobile) Figure 2 is a schematic perspective view showing one embodiment of a mobile body equipped with the photoelectric conversion element of the present invention. The mobile body 30 comprises the photoelectric conversion element 31 of the present invention and a vehicle body 32 equipped with the photoelectric conversion element 31. The photoelectric conversion element 31 is positioned in a location on the vehicle body 32 that can receive ambient light. If the mobile body 30 is an automobile, it may be positioned on the roof. The electrical energy obtained by the photoelectric conversion element 31 may be used to power the mobile body 30 or other electrical equipment. The electrical energy generated from the power of the mobile body 30 may also be used to power the photoelectric conversion element 31. If the mobile body 30 is an automobile, the frictional energy generated by the brakes may be converted into electrical energy and used to control the photoelectric conversion element 31. The mobile body 30 may be, for example, an automobile, a ship, an aircraft, or a drone. The structure of the body 32 of the mobile body 30 is not particularly limited, but it is preferably made of a high-strength material.

[0038] (building materials) Figure 3 is a schematic perspective view showing one embodiment of a building material equipped with the photoelectric conversion element of the present invention. The building material 40 may be the roof of a building. The building material 40 of this embodiment includes the photoelectric conversion element 41 of the present invention, a protective member 42 for protecting the photoelectric conversion element 41, a heat dissipation member 43, and exterior parts 44a and 44b.

[0039] The building material 40 of the present invention may have a heat dissipation member 43 with a higher thermal conductivity than the photoelectric conversion element 41. When used on roofs, etc., the temperature of the photoelectric conversion element 41 may rise due to sunlight, which may reduce the photoelectric conversion efficiency. By using the heat dissipation member 43, the decrease in photoelectric conversion efficiency can be reduced. Examples of the heat dissipation member 43 include metals, alloys, liquid metals, liquid resins, etc.

[0040] Furthermore, the building material 40 of the present invention may have exteriors 44a and 44b. Exteriors 44a and 44b may have different colors or be the same color. 44a and 44b may be made of the same material or different materials. As the exterior, paint or a transparent substrate may be used. It is preferable to use a material with low light absorption and high heat shielding properties. [Examples]

[0041] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Also, in the following description, "parts" refers to "parts by mass" unless otherwise specified.

[0042] [Preparation of particles mainly composed of phthalocyanine compounds] <Preparation of Particle 1> Process (1) Under a nitrogen flow atmosphere, 5.46 parts of orthophthalonitrile and 45 parts of α-chloronaphthalene were added to a reaction vessel and heated to a temperature of 30°C, which was then maintained. Next, 3.75 parts of gallium trichloride were added at this temperature (30°C). The water concentration of the mixture at the time of addition was 150 ppm. The temperature was then raised to 200°C. Next, under a nitrogen flow atmosphere, the reaction was carried out at 200°C for 4.5 hours, after which it was cooled, and the product was filtered when the temperature reached 150°C. The obtained filtrate was dispersed and washed with N,N-dimethylformamide at a temperature of 140°C for 2 hours, and then filtered. The obtained filtrate was washed with methanol and dried to obtain chlorogallium phthalocyanine particles in a yield of 71%.

[0043] Process (2) 4.65 parts of the chlorogallium phthalocyanine particles were dissolved in 139.5 parts of concentrated sulfuric acid at 10°C, and while stirring, the mixture was dropped dropwise into 620 parts of ice water to reprecipitation. The mixture was then filtered under reduced pressure using a filter press. A No. 5C filter (manufactured by Advantec Co., Ltd.) was used for this process. The resulting wet cake (filtrate) was dispersed and washed with 2% ammonia water for 30 minutes, and then filtered using a filter press. Next, the resulting wet cake (filtrate) was dispersed and washed with deionized water, and the filtration process using a filter press was repeated three times. Finally, freeze-drying was performed to obtain hydroxygallium phthalocyanine particles (hydrated hydroxygallium phthalocyanine particles) with a solid content of 23% by mass in yield of 71%. The hydroxygallium phthalocyanine particles were dried using a hyper-dry dryer (product name: HD-06R, frequency (oscillation frequency): 2455MHz ± 15MHz, manufactured by Nippon Biocon Co., Ltd.) to obtain hydroxygallium phthalocyanine particles (crystals) with a moisture content of 1.0% by mass or less.

[0044] Process (3) Five parts of the hydroxygallium phthalocyanine particles were dispersed for 6 hours using a sand mill (K-800, manufactured by Igarashi Machinery Manufacturing (now AIMEX), with a disc diameter of 70 mm and 5 discs) containing five parts of DMF solvent and five parts of glass beads, followed by filtration and drying to obtain particle 1.

[0045] Furthermore, by varying the dispersion time and the amount of glass beads in step (3), particles 2 to 16, shown in Table 1, with different particle sizes and crystallinity, were produced. In Table 1, "Pc compound" refers to a phthalocyanine compound.

[0046] [Table 1]

[0047] (Example 1) [Cleaning of the substrate and the second electrode] An ITO-coated glass substrate (manufactured by Geomatec) was ultrasonically cleaned with pure water, acetone, and methanol in that order for 10 minutes each, and then dried. After that, the ITO-coated glass substrate was subjected to UV ozone treatment for 20 minutes.

[0048] [Formation of the electron transport layer] A titanium isopropoxide ethanol solution adjusted to 2% by mass was applied to the ITO-coated glass substrate by spin coating, and then fired at 400°C for 10 minutes to form a thin-film electron transport layer with a thickness of 20 nm. Furthermore, a titanium dioxide paste containing polyisobutyl methacrylate as an organic binder, titanium dioxide (average particle size 25 nm), and ethanol was applied to the thin-film electron transport layer by spin coating, and then fired at 500°C for 10 minutes to form a porous electron transport layer with a thickness of 500 nm.

[0049] [Formation of the photoelectric conversion layer] A photoelectric conversion layer coating solution was prepared by dissolving 4 g of lead iodide and 1.4 g of methylammonium iodide in 4.5 g of dimethylformamide as a solvent, and stirring at 60°C for 24 hours. A photoelectric conversion layer with a thickness of 500 nm was formed by spin-coating this coating solution onto the electron transport layer. At this time, the maximum surface roughness height Rz of the photoelectric conversion layer was 270 nm.

[0050] [Formation of particle layer] 5g of particle 1 from Table 1, 45g of chlorobenzene, and 50g of glass beads were sealed in a glass bottle and dispersed using a paint shaker for 6 hours to prepare a particle layer coating solution. This solution was then spin-coated onto the photoelectric conversion layer to form a particle layer consisting only of particles with a thickness of 100nm.

[0051] [Introduction of charge transport material into particle layer] Spiro-OMeTAD (180 mg) as a charge transport material was dissolved in chlorobenzene (1 mL). To this chlorobenzene solution, an acetonitrile solution (37.5 μL) prepared by dissolving lithium-bis(trifluoromethanesulfonyl)imide (170 mg) in acetonitrile (1 mL) and t-butylpyridine (TBP, 17.5 μL) were added and mixed to prepare a charge transport material solution. This solution was then applied by spin coating onto a particle layer formed solely of the above particles to create a particle layer with a total thickness of 200 nm, in which the particles were covered with the charge transport material.

[0052] [Formation of the first electrode] On the aforementioned particle layer, a layer with a thickness of 80 nm and an area of ​​0.09 cm² 2 A gold electrode was formed by vacuum deposition to obtain a photoelectric conversion element.

[0053] (Example 2) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 4 was used as particles mainly composed of a phthalocyanine compound, and a particle layer with a thickness of 700 nm was formed using only particles without using a charge transport material.

[0054] (Example 3) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 10 was used as a particle mainly composed of a phthalocyanine compound.

[0055] (Example 4) A photoelectric conversion element was obtained in the same manner as in Example 3, except that the maximum surface roughness height Rz of the photoelectric conversion layer was 190 nm.

[0056] (Example 5) A photoelectric conversion element was obtained in the same manner as in Example 3, except that the maximum surface roughness height Rz of the photoelectric conversion layer was 300 nm.

[0057] (Example 6) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 3 was used as a particle mainly composed of a phthalocyanine compound.

[0058] (Example 7) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 9 was used as a particle mainly composed of a phthalocyanine compound.

[0059] (Example 8) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 8 was used as a particle mainly composed of a phthalocyanine compound.

[0060] (Example 9) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 2 was used as a particle mainly composed of a phthalocyanine compound.

[0061] (Example 10) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 5 was used as a particle mainly composed of a phthalocyanine compound.

[0062] (Example 11) A photoelectric conversion element was obtained in the same manner as in Example 2, except that a particle layer consisting only of particles was formed in the same manner as in Example 1, and then a charge transport material was introduced to form the particle layer. The total thickness of the particle layer was made 100 nm thicker than the thickness of the particles alone.

[0063] (Example 12) A photoelectric conversion element was obtained in the same manner as in Example 2, except that the particle layer thickness was set to 500 nm.

[0064] (Example 13) A photoelectric conversion element was obtained in the same manner as in Example 2, except that the particle layer thickness was set to 40 nm and particle 5 was used as a particle mainly composed of a phthalocyanine compound.

[0065] (Example 14) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 6 was used as a particle mainly composed of a phthalocyanine compound.

[0066] (Example 15) A photoelectric conversion element was obtained in the same manner as in Example 2, except that particle 7 was used as a particle mainly composed of a phthalocyanine compound.

[0067] (Example 16) A photoelectric conversion element was obtained in the same manner as in Example 2, except that the particle layer thickness was set to 400 nm.

[0068] (Example 17) A photoelectric conversion element was obtained in the same manner as in Example 9, except that a particle layer consisting only of particles was formed in the same manner as in Example 1, and then a charge transport material was introduced to form a particle layer. The total thickness of the particle layer was made 100 nm thicker than the thickness of the particles alone.

[0069] (Example 18) A photoelectric conversion element was obtained in the same manner as in Example 9, except that the particle layer thickness was set to 200 nm.

[0070] (Example 19) A photoelectric conversion element was obtained in the same manner as in Example 18, except that a particle layer consisting only of particles was formed in the same manner as in Example 1, and then a charge transport material was introduced to form a particle layer. The total thickness of the particle layer was made 100 nm thicker than the thickness of the particles alone.

[0071] (Example 20) [Cleaning of circuit boards] The glass substrate was ultrasonically cleaned with pure water, acetone, and methanol in that order for 10 minutes each, and then dried.

[0072] [Formation of the second electrode] An Al electrode with a thickness of 1000 nm was formed on the aforementioned glass substrate by vacuum deposition.

[0073] [Formation of the electron transport layer] A tin oxide dispersion aqueous colloid solution (manufactured by Alfa Aesar) was spin-coated onto the aforementioned Al electrode, and an electron transport layer with a thickness of 50 nm was formed by drying at 150°C for 30 minutes.

[0074] [Formation of photoelectric conversion layer and particle layer] The procedure was carried out in the same manner as in Example 1.

[0075] [Formation of the first electrode] Using an ITO target doped with 5% by mass of tin on the aforementioned particle layer, and using Ar gas containing O2 (5 mol%), at a pressure of 0.5 Pa, a sputtering method was used to create a particle with a thickness of 150 nm and an area of ​​0.09 cm². 2 An ITO electrode was formed.

[0076] (Example 21) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 11 was used as a particle mainly composed of a phthalocyanine compound.

[0077] (Example 22) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 12 was used as a particle mainly composed of a phthalocyanine compound.

[0078] (Example 23) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 13 was used as a particle mainly composed of a phthalocyanine compound.

[0079] (Example 24) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 14 was used as a particle mainly composed of a phthalocyanine compound.

[0080] (Example 25) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 15 was used as a particle mainly composed of a phthalocyanine compound.

[0081] (Example 26) A photoelectric conversion element was obtained in the same manner as in Example 1, except that particle 16 was used as a particle mainly composed of a phthalocyanine compound.

[0082] (Comparative Example 1) [Cleaning of the substrate and the second electrode] The procedure was carried out in the same manner as in Example 1.

[0083] [Formation of the injection layer] A LiF film with a thickness of 0.5 nm was formed on the second electrode by vacuum deposition.

[0084] [Formation of bulk heterolayer] A coating solution for the bulk heterolayer was prepared by dissolving and dispersing 1 g of poly(3-hexylthiophene), 1 g of a fullerene derivative (PCBM: Phenyl-C61-Butyric-Acid-Methyl Ester), 8 g of particle 1, and 15 g of chlorobenzene. A bulk heterolayer with a thickness of 300 nm was formed by spin-coating the above coating solution onto the injection layer.

[0085] [Formation of the first electrode] The procedure was carried out in the same manner as in Example 1.

[0086] (Comparative Example 2) [Cleaning of circuit boards] The titanium substrate was ultrasonically cleaned with pure water, acetone, and methanol in that order for 10 minutes each, and then dried.

[0087] [Formation of the second electrode] The procedure was carried out in the same manner as in Example 20.

[0088] [Formation of electron transport layer and photoelectric conversion layer] The procedure was carried out in the same manner as in Example 1.

[0089] [Formation of a charge transport layer] A coating solution for the charge transport layer was prepared by dissolving 1 g of Phthalocyanine (purified by sublimation) [for organic electronics] (manufactured by TCI) in 9 g of chlorobenzene. A charge transport layer with a thickness of 100 nm was formed by spin-coating this coating solution onto the photoelectric conversion layer.

[0090] [Formation of the first electrode] The procedure was carried out in the same manner as in Example 20.

[0091] <Rating> The following evaluations were performed on the photoelectric conversion elements obtained in each example and comparative example.

[0092] (Evaluation of power generation efficiency) A power supply (KEITHLEY, Model 236) is connected between the electrodes of the photoelectric conversion element, and the intensity is set to 100 mW / cm². 2 The photoelectric conversion efficiency was evaluated by irradiating a constant amount of light using a solar simulator (manufactured by Yamashita Densou Co., Ltd.) and measuring the generated current and voltage. The results are shown in Table 2.

[0093] [Table 2] [Explanation of symbols]

[0094] 1, 31, 41: Photoelectric conversion element, 2: Substrate, 3: Second electrode, 5: Photoelectric conversion layer, 6: Particle layer, 7: First electrode, 30: Mobile body, 32: Machine body, 40: Building material, 42: Protective member, 43: Heat dissipation member

Claims

1. A photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer containing an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, A particle layer is provided between the photoelectric conversion layer and the first electrode, the particles of the particle layer contain a phthalocyanine compound in an elemental analysis ratio of 50% by mass or more, A photoelectric conversion element, wherein the phthalocyanine compound contains Ga or Ti.

2. A photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer including an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, A particle layer is provided between the photoelectric conversion layer and the first electrode, the particle layer is a layer formed using particles containing a phthalocyanine compound in an elemental analysis ratio of 50% by mass or more, A photoelectric conversion element, wherein the phthalocyanine compound contains Ga or Ti.

3. A photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer including an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, A particle layer is provided between the photoelectric conversion layer and the first electrode, the particle layer is a layer formed by depositing a phthalocyanine compound in a particle state, A photoelectric conversion element, wherein the phthalocyanine compound contains Ga or Ti.

4. A photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer including an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, A particle layer is provided between the photoelectric conversion layer and the first electrode, the particle layer is a layer formed by dispersing particles having a phthalocyanine compound in an organic solvent and applying the resulting dispersion onto the photoelectric conversion layer, The photoelectric conversion device, wherein the phthalocyanine compound contains Ga or Ti.

5. The photoelectric conversion element according to claim 1, wherein the phthalocyanine compound contains Ga.

6. A photoelectric conversion element according to any one of claims 1 to 5, characterized in that the phthalocyanine compound is hydroxygallium phthalocyanine.

7. 7. The photoelectric conversion element according to claim 1, wherein the average particle size of the particles is smaller than a maximum height Rz of surface roughness of the photoelectric conversion layer.

8. 8. The photoelectric conversion element according to claim 1, wherein the particles have an average particle size of 300 nm or less.

9. 9. The photoelectric conversion element according to claim 1, wherein the particles have an average particle size of 20 nm or more.

10. 10. The photoelectric conversion element according to claim 1, wherein the particle layer has a thickness of 20 nm to 800 nm.

11. 10. The photoelectric conversion element according to claim 1, wherein the particle layer has a thickness of 50 nm to 400 nm.

12. The photoelectric conversion element according to any one of claims 1 to 11, characterized in that the particles contain crystal particles of the phthalocyanine compound of a crystalline type that shows peaks at Bragg angles 2θ of 7.4°±0.3° and 28.2°±0.3° in an X-ray diffraction spectrum using CuKα radiation.

13. The photoelectric conversion element according to any one of claims 1 to 12, characterized in that the particles contain crystal particles of the phthalocyanine compound having a peak of 20 nm to 50 nm in a crystal particle size distribution measured using small-angle X-ray scattering, and a half-value width of the peak is 50 nm or less.

14. 14. The photoelectric conversion element according to claim 1, wherein the particles contain the phthalocyanine compound in an amount of 80% by mass or more and 99% by mass or less in terms of an elemental analysis ratio.

15. A photoelectric conversion element having a first electrode, a second electrode, and a photoelectric conversion layer including an organic-inorganic perovskite compound disposed between the first electrode and the second electrode, the unevenness occurring in the photoelectric conversion layer is filled with particles of a phthalocyanine compound; A photoelectric conversion element, wherein the phthalocyanine compound contains Ga or Ti.

16. The photoelectric conversion element according to claim 1, 3 or 15, characterized in that the particles are covered with a charge transport material.

17. The photoelectric conversion element according to claim 2, characterized in that the particle layer is a layer formed using the particles and a charge transport material.

18. The photoelectric conversion element described in claim 4, characterized in that the particle layer is a layer formed by dispersing particles having the phthalocyanine compound in an organic solvent, applying the dispersion onto the photoelectric conversion layer, and further applying a charge transport material solution.

19. A photoelectric conversion module comprising a plurality of the photoelectric conversion elements according to claim 1 .

20. A photoelectric conversion device comprising: the photoelectric conversion element according to claim 1 ; and a power storage section connected to the photoelectric conversion element.

21. A photoelectric conversion device comprising: the photoelectric conversion element according to claim 1 ; and an inverter connected to the photoelectric conversion element.

22. A moving object comprising: the photoelectric conversion element according to claim 1 ; and a body having the photoelectric conversion element.

23. A building material comprising: the photoelectric conversion element according to claim 1 ; a protective member for protecting the photoelectric conversion element; and a heat dissipation member.